Natural products targeting clinically relevant enzymes - Andrade, Paula B.; Valentao, Patricia; Pereira, David M. (Weinheim, Germany : Wiley-VCH, 2017)
The past decade has seen the reappearance of natural products as a valuable source of potent therapeutics. Here, experts on bioactive natural products cover the full spectrum of clinically relevant enzymes that are known to be targeted by natural products. Key enzymes include acetylcholine esterase, angiotensin-I-converting enzyme, cyclooxygenase, dihydrofolate reductase, phospholipase A2, respiratory complexes, and many more. By connecting the diversity of medicinal natural product sources with their potential clinical applications, this volume serves as a companion for the medicinal chemist looking for innovative small molecule compounds as well as for pharmacologist interested in the clinical effects and mode of action of herbal and traditional medicines.
Chapter 3 Natural Angiotensin Converting Enzyme (ACE) Inhibitors with Antihypertensive Properties3.1 Introduction; 3.2 Mechanisms of Blood Pressure Regulation; 3.2.1 Renin-Angiotensin-Aldosterone System; 3.3 The Treatment of Hypertension; 3.3.1 Angiotensin Converting Enzyme Inhibitors; 3.4 Natural Products as Angiotensin Converting Enzyme Inhibitors; 3.4.1 Polyphenols; 3.4.2 Protein Derived Peptides; 3.5 Conclusions; References; Chapter 4 Phospholipase A2 Inhibitors of Marine Origin; 4.1 Relevance of Marine Organisms; 4.2 Inflammation; 4.2.1 Phospholipase A2
Includes bibliographical references.
Online resource; title from PDF title page (EBSCO, viewed September 11, 2017).
Keywords: Enzymes -- Effect of drugs on; Natural products -- Therapeutic use; Bioactive compounds; MEDICAL / Physiology; SCIENCE / Life Sciences / Human Anatomy & Physiology; Bioactive compounds; Enzymes -- Effect of drugs on; Natural products -- Therapeutic use; Electronic books; Electronic books